Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Efficient frequency conversion by combined photonic–plasmonic mode coupling - Weber, N.; Hoffmann, S. P.; Albert, M.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Morphology, structure and enhanced PL of molecular beam epitaxial In0.2Ga0.8As layers on nanopillar patterned GaAs - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Weber, N.; Meier, Cedrik; Schierholz, R.; Lindner, Jörg

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Fabrication of fully undercut ZnO-based photonic crystal membranes with 3D optical confinement - Hoffmann, Sandro Phil; Albert, Maximilian; Meier, Cedrik (Superlattices and Microstructures)

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Nonlinear optical sub-bandgap excitation of ZnO-based photonic resonators - Bader, Christina A.; Zeuner, Franziska; Bader, Manuel H. W.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Optical spectrum, perceived color, refractive index, and non-adiabatic dynamics of the photochromic diarylethene CMTE - Wiebeler, Christian; Bader, Christina A.; Meier, Cedrik; Schumacher, Stefan (Phys. Chem. Chem. Phys.)

Structural enhancement of ZnO on SiO2 for photonic applications - Ruth, Marcel; Meier, Cedrik (AIP Advances)

Whispering gallery modes in zinc-blende AlN microdisks containing non-polar GaN quantum dots - Bürger, M.; Ruth, M.; Declair, S.; Förstner, Jens; Meier, Cedrik; As, Donat Josef (Applied Physics Letters)
Whispering gallery modes (WGMs) were observed in 60 nm thin cubic AlN microdisk resonators containing a single layer of non-polar cubic GaN quantum dots. Freestanding microdisks were patterned by means of electron beam lithography and a two step reactive ion etching process. Micro-photoluminescence spectroscopy investigations were performed for optical characterization. We analyzed the mode spacing for disk diameters ranging from 2-4 lm. Numerical investigations using three dimensional finite difference time domain calculations were in good agreement with the experimental data. Whispering gallery modes of the radial orders 1 and 2 were identified by means of simulated mode field distributions.
Keywords: tet_topic_qd; tet_topic_microdisk

Blue-green emitting microdisks using low-temperature-grown ZnO on patterned silicon substrates - Ruth, Marcel; Zentgraf, Thomas; Meier, Cedrik (Optics Express)

Scaling coefficient for three-dimensional grain coalescence of ZnO on Si(111) - Ruth, Marcel; Meier, Cedrik (Physical Review B)